An efficient thermal interface material with anisotropy orientation and high through-plane thermal conductivity. (5th January 2023) - Zhang, Guorui; Xue, Sen; Chen, Feng; Fu, Qiang
Abstract: The rapid development of integrated circuits and electronic devices with increased power density and heat flux, requires effective heat dissipation for thermal management. Constructing a directional thermal pathway from the vertically aligned thermal conductive fillers in the thickness-direction of polymer-based thermal interface materials (TIMs) is a desirable strategy to form materials with high thermal conductivity. However, due to the complexity of vertical orientation technology, fillers with the poor orientation degree weaken the enhancement of through-plane thermal conductivity. In this work, we prepared short carbon fiber (CF)/olefin block copolymer (OBC) composites with high orientation degree via the melting extrusion method on a basis of sharing force induce alignment. Attributed to the high orientation degree of CF in the vertical direction, the as-prepared material shows a through-plane thermal conductivity (κ⊥ ) up to 15.06 W/m K at a 30 vol% CF content, which is ∼10 times that of a parallel structure. The operating temperature difference between vertical and random reached 35.2 °C, surpassing the characters in most works of literature. This study provides an effective way to develop high-oriented degree and electrical insulation polymer composites with superior κ⊥ for scalable thermal management applications in electronic devices. Graphical abstract: Image 1 Highlights: A facile and efficient method to obtain high orientation for polymer-based TIMs. Excellent through-plane thermal conductivity is obtained via constructing vertical structure. Outstanding thermal management capability is achieved as an efficient TIM.